Research of the Robust Design of New Type of Disc Brake based on Uncertainty Theory - Sun Hong (Jixie chuandong)
Aiming at the problems of traditional disk brake in design process high artificially randomness and design results conservative,a disc brake is regarded as the research object,the uncertainty theory and response surface model is introduced into the design process,and the brake temperature change and the amount of braking brake distance change are also regarded as the main basis of design,the optimization calculation workload is simplified by using the preference aggregation method. Finally,the result of robust design analysis is verified by the analysis of braking distance and braking temperature. The results show that,through the calculation of the pareto solution set of braking distance and temperature and selecting a reasonable combination of μf,δf,the robust design model parameter can be obtained,the efficiency of design is greatly improved. Through the finite element analysis of the disc brake model of robust design,the strength and temperature of model are all meet the model using requirements.